Strategic behavior within families of hedge funds - Kolokolova, Olga (Journal of Banking & Finance, 2011)
The paper investigates the strategic behavior of hedge fund families. It focuses on decisions to start and liquidate family-member funds. Hedge fund families tend to liquidate funds that underperform compared to other member funds, and to replace them by new ones. By choosing a launch time after a short period of superior performance by their member funds, families extend the spillover to new funds. Hedge fund families seem to be more experienced in promoting their funds and attracting fund inflow than in generating superior performance. This results in higher dollar compensation earned by managers within multi-fund families than in stand-alone funds.